Merekonstruksi Epistemologi Ibrahim - Kipling, Rudyard (Unisia, 2016)
The modern politician, Samuel P. Huntingthon has stated that at the age XXI will enter the calsh of civilization. In fact, not all of scientist agree with Huntingthon, for example John L. Esposito has declared that Islam is not the threat but it will become the dynamic challenge to solve civilization in the future. In this sense, the writer has optimistic that needed is to epistemology reconstruction. This is the main reasons and that of reference. Hence, the epistemology of Ibrahim should be an altemative.